ANALISIS RAGAM DIALOG DIAGNOSIS PENYAKIT BERBASIS SPK MODEL TAM DENGAN SEMPLS - Sandi Justitia Putra; Jian Budiarto; Jihadil Qudsi (Universitas Bumigora, 2018)
Decision Support System provides problem solving with semi structured and unstructured conditions. Decision Support System also has a role in the medical world, used in diagnosing diseases based on examination of patients. But often occurs less implementation due to the system interface interface that is not in accordance with the wishes of users. System interface interface tested there are 3 stages, namely anamnesis stage, physical examination stage, and examination. The choices given to the respondents are 3 interface design with various dialogue techniques for the anamnesis and physical examination phase ie Natural Language Process, Menu System and Filling Form and 2 interface design for supporting investigation ie Windowing System and Graphic Interaction. After the respondents made a choice on the questionnaire sheet, statistical tests were performed based on the Technology Acceptance Model. The result of the analysis shows the design according to the respondent's wishes on the decision support system to diagnose the disease at the anamnesis stage and physical examination stage is the design of the interface system with the filling form because of the larger R square model value at each stage of the interface design Natural Language Process and Menu System , while the supporting stage is the graphical interface interaction design on the graphical display, because of the larger R square model values ​​at each stage of the windowing system interface design.